Evaluation Of Integrated Antenatal Care Implementation With Cipp Model In The Work Area - Feby Irania; Chrismis Novalinda Ginting; Masryna Siagian (CV. Inara, 2022)
Antenatal care is health services which is given by professional health workers to increase the health status of pregnant women and their fetus that doing according to the standard of antenatal care which can detect earlier the deviation and the risk whichmight be occured in pregnancy in order that could be overcomed fast and appropriately. Puskesmas Bagan Batu is not appropriate with standard of antenatal care lack of the knowledge and obedience of midwives, instruments and infrastructure. The purpose of the research was to evaluate the implementation of integrated antenatal care by CIPP model in the work area of Puskesmas Bagan Batu. The research used qualitative method, by in-depth interviews, conducting observation, and document study with 8 informan that consisted of Head of Puskesmas, doctor of program holder KIA, coordinator midwive, 3 midwives in poli KIA, 3rd trimester pregnant women with complete inspection in Puskesmas Bagan Batu, and 3rd trimester pregnant woman with incomplete inspection in Puskesmas Bagan Batu. The result of the research showed that only 2 of the midwives got antenatal care training, instrument and infrastructure can improve more better, midwives had not knowledge and obedience to use the new standard of antenatal care services optimally. So, the process which include the implementation of antenatal care was not according by the standard. The coverage of antenatal care has decreased in the last three years. While coverage of tablet Fe has increased significantly, and the coverage of tetanus toxoid imunization has not increased at all and very far below the standard. It was recommended that public regional of Puskesmas Bagan Batu increase some aspects of input iclude of personal quality, midwives obedience, instrument and infrastructure. And then the aspect of process for the implementation of antenatal care according to the standard to achieve the best result for the quality of antenatal care.